Solving the Students’ Problems in Writing Argumentative Essay Through the Provision of Planning - Lestari Setyowati; Sony Sukmawa; Mohamad Anan Latief (Soegijapranata Catholic University, 2017)
Most Indonesian students who are learning English often consider writing as not only the most difficult skill to master, but also a demanding activity. To help them cope these problems, the application of planning in the writing process seems to be a solution. This study attempts to find out howdifferent planning formats can improve EFL students’ writing performance in argumentative essays. The subjects of the studywere the fourth semester students taking essay writing class. The research was conducted from May to June 2015, consisting of three cycles in Classroom Action Research design by using different planning types, namely rough drafting and outlining strategy in which each cycle consisted of two meetings.The students’ compositions were measured by using primary trait scoring rubric for argumentative essay. The result of the study shows that the provision of planning is effective to improve the students’ performance in writing argumentative essay. The effectiveness of different types planningdepends on the students’ preference of which to use.